Short‐Selling Risk - ENGELBERG, JOSEPH E.; REED, ADAM V.; RINGGENBERG, MATTHEW C. (Journal of Finance, 2018)
ABSTRACT Short sellers face unique risks, such as the risk that stock loans become expensive and the risk that stock loans are recalled. We show that short‐selling risk affects prices among the cross‐section of stocks. Stocks with more short‐selling risk have lower returns, less price efficiency, and less short selling.